2010
DOI: 10.1073/pnas.1006008107
|View full text |Cite
|
Sign up to set email alerts
|

Rapid weight gain after birth predicts life history and reproductive strategy in Filipino males

Abstract: Ecological cues during prenatal and postnatal development may allow organisms to adjust reproductive strategy. The hypothalamicpituitary-gonadal (HPG) axis is a prime candidate for adaptive plasticity as a result of its critical period of birth to 6 mo (B6M) in humans and the role of testosterone in the development and maintenance of costly sexually dimorphic somatic and behavioral traits. We hypothesized that weight velocity specific to B6M would predict male life history characteristics, including maturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
104
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(124 citation statements)
references
References 85 publications
(81 reference statements)
12
104
2
Order By: Relevance
“…Similar responses to developmental food deprivation have been found throughout the animal kingdom (Lee and Zucker, 1988;Applebaum and Heifetz, 1999;Simpson et al, 1999;Krause et al, 2009;Mitchell et al, 2009;Kuzawa et al, 2010;van den Heuvel et al, 2013). Our study also suggests that mechanisms involved in the responses to larval nutritional stress imposed by nurse bees (young adult workers that feed the larvae) play a key role in honey bee division of labor (Page, 2013).…”
Section: Stress Response and Division Of Labor In Honey Beessupporting
confidence: 71%
See 2 more Smart Citations
“…Similar responses to developmental food deprivation have been found throughout the animal kingdom (Lee and Zucker, 1988;Applebaum and Heifetz, 1999;Simpson et al, 1999;Krause et al, 2009;Mitchell et al, 2009;Kuzawa et al, 2010;van den Heuvel et al, 2013). Our study also suggests that mechanisms involved in the responses to larval nutritional stress imposed by nurse bees (young adult workers that feed the larvae) play a key role in honey bee division of labor (Page, 2013).…”
Section: Stress Response and Division Of Labor In Honey Beessupporting
confidence: 71%
“…In mammals, under-nutrition or over-nutrition during the prenatal or postnatal period can impact adult reproductive capability (reviewed by Gardner et al, 2009), which may reflect an adaptive adjustment of reproductive strategy (Rae et al, 2002;Rhind, 2004;Jasienska et al, 2006;Kuzawa et al, 2010). In general, a strategy of reducing reproductive investment while increasing somatic maintenance is a typical survival mechanism in insects (Elkin and Reid, 2005;García-Roger et al, 2006).…”
Section: Discussion Adaptive Responses To An Anticipatory Starvationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective investigation of 994 Filipino girls, every month of exclusive breastfeeding was associated with a 6% lower probability of menarche over the followup period after adjusting for socioeconomic, maternal, and birth characteristics (3). Contrary to these studies, an investigation of 770 Filipino boys found that those who were breastfed as infants had a faster height velocity from birth to 6 months, which was inversely associated with pubertal maturation, than did boys who were not breastfed (56).…”
Section: Infant Feedingmentioning
confidence: 74%
“…Neither fast nor slow strategies are inherently better. Instead, the evolutionary benefit of a given strategy depends on the environment in which an individual develops (Belsky, 1997;Belsky et al, 1991;Caudell & Quinlan, 2012;Kuzawa, McDade, Adair, & Lee, 2010;Simpson & Belsky, 2008, in press). Belsky et al (1991) were the first to specify how lifehistory strategies should unfold across the life span.…”
mentioning
confidence: 99%